Comparative study to pseudomonas aeruginosa isolated from infected caws Gentealia and the soil and determine its resistant to some antibiotics and its produce siderophors compounds - R.E, AL-Shweely J.; H.J.K.‎, AL-Jawad (The Iraqi Journal of Veterinary Medicine, 2009)
This study was conducted to compare pseudomonas aeruginosa strains which obtained from the soil ofAL-Qadisiya governorate with the strains of cows infected by metritis in the vet hospital AL-Qadisiyafor (9) antibiotics ; Ciprofloxacin Erythromycin, Streptomycin, Gentamycin, Tetracyclin,Chloramphenical , Rifampicin, Nalidixic acid, Lincomycin, and ability of these strains to producesiderphores compounds. The results of the strains which loslated from pathological cases showed highratio of resistanace to most of antibiotics which used in the study except ciprofloxacin .where thestrains which loslated from the soil was resistance to tetracyclin and Lincomycin and showeddifferential degrees of sensitivity to others the ciprofloxacin came at first. the result of this study alsoshowed the strains from pathological caese could produce siderophorse compound where was all strainwhich lsolated from the soil of AL-Qadisiya give negative test for producing siderophores compounds